The Determinants of Total Assets of Sharia Commercial Banks in Indonesia - Herlitah; Nadia Afrilliana; Siti Khoirina (Peradaban Journal of Economic and Business, 2022)
The purpose of this study is to analyze the factors that affect the total assets of Islamic commercial banks in Indonesia. This research data is time series data from January 2015 to September 2021 in the form of monthly results and processed using multiple linear regression. The results of this study indicate that the variables NPF, FDR, Number of Offices, Number of Workers, Inflation and Exchange Rate together affect the variable Total Assets of Islamic Commercial Banks